From convoy to parting ways? Post-crisis divergence between European and US macroeconomic policies - Jean Pisani-Ferry; Adam S. Posen (Bruegel, 2011)
The response in 2008-09 to the global financial crisis was in many ways a high water mark for transatlantic policy coordination. The major economies of the EU and the US rapidly agreed on a series of measures to limit the crisis. However, the common approach has since unraveled. This paper explores why the 'London consensus' has not survived for much more than a year. We identify four non-competing explanations: (a) divergence in economic developments, especially the productivity response to the recession; (b) domestic political economy factors, notably the pressure to act against unemployment in the US; (c) differences in beliefs as regards the nature of the recovery from the common shock, about which there is much more supplyside optimism in the US ; (d) institutional factors such as the lack of a central fiscal authority in the EU. In response to this situation we suggest a critical quantum of coordination. Key measures include a commitment to avoiding deliberate currency depreciation and unilateral intervention; agreement to give the IMF an enhanced monitoring role; the adoption by parliaments of medium-term fiscal plans ; and cooperation on the issue of Chinese undervaluation.
Keywords: 330; Finanzkrise; Wirtschaftswachstum; Wirtschaftspolitik; Geldpolitik; Finanzpolitik; Internationale Wirtschaftspolitik; EU-Staaten; USA